When is the best time to screen for perinatal anxiety? A longitudinal cohort study - Ayers, S; Sinesi, A; Coates, R; Cheyne, H; Maxwell, M; Best, C; McNicol, S; Williams, LR; Uddin, N; Shakespeare, J; Alderdice, F (Elsevier, 2024)
Background For screening for anxiety during pregnancy and after birth to be efficient and effective it is important to know the optimal time to screen in order to identify women who might benefit from treatment. Aims To determine the optimal time to screen for perinatal anxiety to identify women with anxiety disorders and those who want treatment. A secondary aim was to examine the stability and course of perinatal anxiety over time. Methods Prospective longitudinal cohort study of 2243 women who completed five screening questionnaires of anxiety and mental health symptoms in early pregnancy (11 weeks), mid-pregnancy (23 weeks), late pregnancy (32 weeks) and postnatally (8 weeks). Anxiety and mental health questionnaires were the GAD7, GAD2, SAAS, CORE-10 and Whooley questions. To establish presence of anxiety disorders diagnostic interviews were conducted with a subsample of 403 participants. Results Early pregnancy was the optimal time to screen for anxiety to identify women with anxiety disorders and women wanting treatment at any time during pregnancy or postnatally. These findings were consistent across all five questionnaires of anxiety and mental health. Receiving treatment for perinatal mental health problems was most strongly associated with late pregnancy and/or postnatal assessments. Anxiety symptoms were highest in early pregnancy and decreased over time. Conclusion Findings show that screening in early pregnancy is optimal for identifying women who have, or develop, anxiety disorders and who want treatment. This has clear implications for practice and policy for anxiety screening during the perinatal period.